Understanding Creutzfeldt-Jackob disease from a viewpoint of amyloidogenic evolvability. Issue 1 (1st January 2020) - Hashimoto, Makoto; Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Waragai, Masaaki; Masliah, Eliezer; Takenouchi, Takato
ABSTRACT: Creutzfeldt-Jackob disease (CJD), the most common human prion disorder, is frequently accompanied by ageing-associated neurodegenerative conditions, such as Alzheimer's disease and Parkinson's disease. Although cross-seeding of amyloidogenic proteins (APs), including amyloid β and α-synuclein, may be critical in the co-morbidity of neurodegenerative disorders, the direct interaction of APs with prion protein (PrP), the central molecule involved in the pathogenesis of CJD, is unlikely. Currently, the nature of this biological interaction and its significance remain obscure. In this context, the objective of the present study is to discuss such interactions from the perspective of amyloidogenic evolvability, a putative function of APs. Hypothetically, both hereditary- and sporadic CJD might be attributed to the role of PrP in evolvability against multiple stressors, such as physical stresses relevant to concussions, which might be manifest through the antagonistic pleiotropy mechanism in ageing. Furthermore, accumulating evidence suggests that PrP- and other APs evolvability may negatively regulate each other. Provided that increased APs evolvability might be beneficial for acquired CJD in young adults, a dose-reduction of α-synuclein, a natural inhibitor of αS aggregation, might be therapeutically effective in upregulating APs evolvability. Collectively, a better understanding of amyloidogenic evolvability may lead to the development of novel therapies for CJD.